Disseminated mycobacterium avium complex infection mimicking lymphoproliferative disorder in a kidney transplant recipient - Turgut, Didem; Cansu Alperen, Cemile; Handan Ozdemir, Binnaz; Haberal, Mehmet (Annals of Medical Research, 2021)
None
Keywords: Disseminated mycobacterium avium complex; kidney; transplant